New directions in biblical theology : papers of the Aarhus Conference, 16-19 September 1992 - Pedersen, Sigfred, 1932- (Novum Testamentum, Supplements, 1994)
New Directions in Biblical Theology contains the papers of an international conference on Biblical Theology which was organized by the Faculty of Theology of Aarhus University on the occasion of its 50th anniversary. The papers delivered at the conference address a number of fundamental issues evolving from the recently revived debate on Biblical Theology. The first group of contributions deals with essential topics such as the biblical concept of revelation, and the interpretation of the Old Testament as presented by the apostle Paul, by the evangelists Matthew, Mark and John, and by the Letter to the Hebrews. Further contributions treat themes such as the 're-use' of a given biblical tradition, theology of creation, apocalyptic, the concept of mercy, the community's role in transmission and interpretation, and the primary aspects of the concept of God.